110k views
2 votes
Solve the system by substitution.
9x + 7y = 33
-6x = y

User Bentham
by
4.8k points

2 Answers

1 vote

Answer:

The answer is (-1, -6)

Explanation:

To get y by itself, you switch sides of the Y and the -6x

9x+7y=33

y= -6x

You then put the -6x where the y is

9x+ 7(-6x) = 33

9x -42x =33 9 -42 = -33

-33x = 33

It's now a one-step equation

x= -1

Now you put the x value (-1) where the x is in y= 6x

y= 6 (-1) y=-6

User Efecarranza
by
5.5k points
3 votes

Answer:

x= -1, y= 6

Explanation:

9x + 7y =33---a

-6x = y---b

Put b into a,

9x + 7(-6x) = 33

9x - 42x = 33

-33x = 33

x = -1----c

put c into b,

-6(-1) = y

y=6

User MaxKlaxx
by
5.0k points